ANALISIS GEOMETRI JALAN TAMBANG AREA LOADING POINT PIT 2 MENUJU STOCKPILE TERHADAP PRODUKTIVITAS ALAT ANGKUT FUSO 220 PS DI CV. DIAN PURNAMA, KABUPATEN SIJUNJUNG, PROVINSI SUMATERA BARAT - Muhammad Shidiq; Rizto Salia Zakri (Departemen Teknik Pertambangan FT UNP, 2022)
A good haul road is a road that can make the haul equipment run optimally. Distance from the front loading pit 2 area to the stockpile is 440 meters which consists of 4 segments. This research will analyze the condition of the Loading Point haul road to the current stockpile in each segment, make an improvement plan so that the haul road condition conforms to predetermined standards, analyze the effect of improving haul road geometry on the travel speed of the Mitsubishi Fuso 220 PS, and analyze the effect of improving haul road geometry on the productivity of the Mitsubishi Fuso 220 PS conveyance. With the haul road analysis, it is known that there is a need to improve the geometry of the haul road on a straight road with an ideal width of 4.92 meters, a bend road of 7.35 meters, the formation of a cross slope of 40 mm/m, making a superelevation so that the height difference that must be made is 0 .29 meters, and the need for haul road pavement. Through these improvements, with a coal production target of 5,000 tons/month, it is known theoretically that productivity from 125.66 tons/hour has increased to 186.92 tons/hour.